APPLICATION OF RANDOMIZED RESPONSE TECHNIQUE ON A SURVEY SAMPLING OF YEAST INFECTION AMONG NIGERIAN FEMALE UNDERGRADUATES - A. O., . Adepetun (university of eloued جامعة الوادي, 2020)
In this paper, randomized response technique was adopted to determine the proportion of female undergraduates at the Federal University of Technology Akure that have had yeast infection at a point in time, the age range that has the most number of yeast infection cases as well as the female hostel with the highest number of yeast infection cases. Questionnaires were used to collect data from the respondents. Z-tests were used in hypothesis testing. All comparisons involving randomized response data used the estimated proportion of girls with yeast infection and the sampling variance to calculate the z-score. The results of the study indicated that Jadesola female hostel has the most number of yeast infection cases proportion 99.8% while the proportion of yeast infection cases in Jibowu hostel is 66.8%. The result also shows that 90% of the female undergraduates between the age range of 16 and 18 years contracted the infection.
artical
Keywords: Randomized response technique, yeast infection, z-test, sensitive characteristic